Relationship of Serum Uric Acid Level with Demographic Features, Risk Factors, Severity, Prognosis, Serum Levels of Vitamin D, Calcium, and Magnesium in Stroke - Payam Saadat; Alijan Ahmadi Ahangar; Mansor Babaei; Mandana Kalantar; Mohammad Ali Bayani; Hiva Barzegar; Hemmat Gholinia; Farbod Zahedi Tajrishi; Sekineh Faraji; Fatemeh Frajzadeh (Stroke Research and Treatment)
Introduction. Stroke is one of the most common neurological disorders with high mortality rates. A large financial burden is imposed on the families and health systems of countries in addition to the problems related to the disabilities caused by the disease for the patients. Extensive research is being conducted on the disease, including studies seeking possible relationships between some biomarkers such as uric acid and stroke. Methods. This descriptive-analytic cross-sectional study was conducted on 170 stroke patients at Babol Ayatollah Rohani Hospital during 2015-2016. Serum uric acid (SUA) levels were measured and recorded at admission time. Patients’ demographic data as well as the stroke type and some of their risk factors were entered in a checklist. The data were analyzed by SPSS.v.23 using chi-square and logistic regression tests. P<0.05 was considered as significant in all analyses. Results. Of the total 170 included patients, 57% had normal, 25% had low, and the remaining patients (18%) had high SUA levels. There was no significant difference in SUA levels in different types of stroke in both genders. Diabetic ischemic embolic patients had higher levels of SUA than diabetic ischemic thrombotic cases. Patients with low magnesium levels had higher rate of low levels of SUA in ischemic stroke. Conclusion. Serum uric acid levels are not associated with stroke types and gender. Diabetic embolic ischemic stroke cases had high SUA levels than thrombotic types and in ischemic stroke patients with low serum levels of magnesium, SUA levels were also lower.